2007
DOI: 10.1002/chin.200717218
|View full text |Cite
|
Sign up to set email alerts
|

Arylmethyl Substituted Derivatives of Fosmidomycin: Synthesis and Antimalarial Activity.

Abstract: Antimalarial activity X 0140Arylmethyl Substituted Derivatives of Fosmidomycin: Synthesis and Antimalarial Activity. -Introduction of an arylmethyl substituent at the α-position of the phosphinic acid moiety of Fosmidomycin and masking the phosphonic acid functionality yield stable, non-hygroscopic Fosmidomycin analogues. Derivative (I) is approximately twice as active as the bis(pivaloyloxymethyl) ester of Fosmidomycin, but less active than the FR900098 prodrug. Since all substituted analogues are tested as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Fosmidomycin ( 1 ), a phosphonate antibiotic with a hydroxamate pharmacophore that was originally isolated from Streptomyces lavendulae , , is known to have antibacterial and herbicidal activity and was more recently shown to be active against the Plasmodium species causing malaria. , Its molecular target, IspC, catalyzes the first committed step in the non-mevalonate isoprenoid biosynthesis pathway that is essential in Plasmodium spp. but absent in mammals (Scheme ). , 1 can cure human malaria and has a favorable toxicity profile but has shortcomings with regard to pharmacokinetic aspects, which prompted structural modifications in several laboratories. Also of note, 1 and its analogs are expected to be exempt from target-related toxicity and from cross-resistance with established antimalarials and may even be able to target the malaria liver stages that are insufficiently addressed by current antimalarials. , We report the synthesis of thia isosters of reversed hydroxamic acid analogs of 1 and their enzymatic, antiparasite, and structural biology features. Furthermore, we show that IspC has a high degree of enantioselectivity for a reverse α-aryl derivative of 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Fosmidomycin ( 1 ), a phosphonate antibiotic with a hydroxamate pharmacophore that was originally isolated from Streptomyces lavendulae , , is known to have antibacterial and herbicidal activity and was more recently shown to be active against the Plasmodium species causing malaria. , Its molecular target, IspC, catalyzes the first committed step in the non-mevalonate isoprenoid biosynthesis pathway that is essential in Plasmodium spp. but absent in mammals (Scheme ). , 1 can cure human malaria and has a favorable toxicity profile but has shortcomings with regard to pharmacokinetic aspects, which prompted structural modifications in several laboratories. Also of note, 1 and its analogs are expected to be exempt from target-related toxicity and from cross-resistance with established antimalarials and may even be able to target the malaria liver stages that are insufficiently addressed by current antimalarials. , We report the synthesis of thia isosters of reversed hydroxamic acid analogs of 1 and their enzymatic, antiparasite, and structural biology features. Furthermore, we show that IspC has a high degree of enantioselectivity for a reverse α-aryl derivative of 1 .…”
Section: Introductionmentioning
confidence: 99%
“…More functionalized lipophilic ester prodrugs (e.g., 52 , Chart ) have been recently reported by Kurz and co-workers displaying significantly better IC 50 values than 11 in P. falciparum growth assays including a drug-resistant strain of P. falciparum ( 52 , IC 50 = 0.022 μM; 11 , IC 50 = 0.81 μM against P. falciparum Dd2) . The antimalarial activity of these reversed derivatives is also better compared to the previously reported pivaloyloxymethyl ester analogues of 11 and 20 . , Further derivatization at the hydroxamic nitrogen atom of 52 does not lead to an improved inhibitory potency.…”
Section: Introductionmentioning
confidence: 78%
“…92 The introduction of other substituents resulting in α-halogenated derivatives, 93 or α-arylmethyl-substituted derivatives, afforded submicromolar activity against various strains of P. falciparum. 94 In particular, several studies have shown that the introduction of phenyl residues with different substitution patterns at the α position of the reverse derivatives 21 or 22 can significantly increase their inhibitory potency of P. falciparum IspC. For example, 36 was found to possess single-digit nanomolar inhibition of P. falciparum IspC (IC 50 = 3.1 nM), compared to the parent compound 20 displaying an IC 50 of 15 nM.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
See 2 more Smart Citations